Shakedown analysis of cyclic plastic deformation characteristics of unbound granular materials under moving wheel loads. (10th April 2018) - Xiao, Yuanjie; Zheng, Keyang; Chen, Liuxin; Mao, Jianfeng
Highlights: The coupling effect of cyclic vertical and horizontal normal stresses was studied. The shakedown concept was used to classify measured plastic deformation behavior. Plastic deformation must be assessed from plastic and resilient strains together. Abstract: Cyclic plastic strain behavior of unbound granular materials (UGMs) exhibits significant stress path dependency. Using a customized triaxial apparatus capable of applying stress path loading, a series of laboratory repeated load triaxial (RLT) tests were conducted on two typical UGMs by varying simultaneously the axial stress and the radial stress. Effects of realistic in-situ stress paths due to a passing wheel on cyclic plastic strain behavior of unbound granular base and subbase materials were investigated and quantified. The analyses of experimental results revealed that the accumulated plastic strain responses of both UGMs subjected to different stress path loadings can be described by the shakedown approach. The amount of accumulated permanent strain, permanent strain rate, and resilient strain were used to classify the plastic deformation accumulation patterns of tested materials under moving wheel loads. Finally, the significance of the research findings on pavement analysis and design practices was highlighted to evaluate permanent deformation resistance of UGMs and their suitability for use in rut resistant and stable pavement foundation layers.